The crisis within : on knowledge and education in India - Devy, G. N., 1950- (Aleph, 2017)
Nearly one in every twelve humans is a young Indian for whom meaningful education is of critical importance. A good education will not only help our youth get jobs and build fulfilling careers, it will also lead to the widening of our collective imagination and the shaping of the way we think; for all these reasons it ought to be an important concern of our time.Unfortunately, this is not the case. There is a lack of infrastructure, adequate funding and genuine autonomy within educational institutions, departments within those institutions and individuals who teach in those departments. And this is not all. There is also the question of the nature of knowledge that is relevant to our rapidly modernizing country that needs to be dealt with.If knowledge is the core of education and if education lays the very foundation of a nation, the author argues that it is of critical importance that the plight of educational institutions and the need to generate knowledge appropriate to India are addressed without any delay.Original and profound, this book offers a clear picture of the mistakes that have been committed in the past, confronts the present decline of knowledge and education in the country and offers a vision for the future.